Efficacy evaluation of a minimally invasive surgical procedure (oblique lateral interbody fusion) for lumbar spinal tuberculosis—retrospective cohort study - Zheng, Ke; Ni, Zhihao; Han, Guosong; Shan, Tao; Xu, Bin (Frontiers in Bioengineering and Biotechnology, 2024)
ObjectiveIn the current study, to demonstrate the advantages of oblique lateral interbody fusion (OLIF), we focused on the therapeutics for lumbar spinal tuberculosis with the comparison of three treatments, including anterior approach, posterior approach, and OLIF combined with posterior percutaneous pedicle screw fixation.MethodsThis study included patients with lumbar spinal tuberculosis from July 2015 to June 2018. We divided these patients into three groups: 35 patients underwent an anterior-only approach (Group A), 36 patients underwent a posterior-only approach (Group B), and 31 patients underwent OLIF combined with posterior percutaneous pedicle screw fixation (Group C). Operation time, blood loss, hospital stays, the visual analog scale (VAS) and the Oswestry disability index (ODI), ASIA grade, the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and Cobb angle were used to evaluate the surgical approaches.ResultsA total of 102 patients joined this study of three therapeutic groups. The mean hospital stays, the mean operative time, and surgical blood loss of the three groups of patients were (14.40 ± 2.6, 14.00 ± 2.51, and 9.39 ± 1.86) days, (177.23 ± 13.23, 198.00 ± 16.75, and 150.39 ± 14.28) minutes, and (307.43 ± 21.91, 406.67 ± 27.02, and 105.97 ± 18.90) mL, respectively. VAS and ODI of all patients significantly improved 1 week after surgery (P < 0.05). As all patients received regular anti-tuberculosis treatment before and after surgery, ESR and CRP indicators maintained at normal levels 1 week after surgery. The Cobb angle was significantly corrected 1 week after surgery (P < 0.05). Eight patients had postoperative complications, and all of them recovered after active treatment.ConclusionOLIF combined with posterior percutaneous pedicle screw fixation has the advantages of less surgical trauma and faster postoperative recovery, although all three surgical approaches can achieve satisfactory clinical results.